Transcriptoma de metacestóide de Taenia saginata - Paulan, Silvana de Cássia [UNESP] (2015)
Taenia saginata represents a threat to food security and public health in consequence of human infection by ingestion of contaminated undercooked meat. This zoonosis is worldwide distributed, affecting human, definitive host, and bovine, intermediate host. Besides, bovine cysticercosis is responsible for significant economic losses due to the condemnation of infected carcasses. The main strategy to control taeniasis-cysticercosis complex consists of interrupting the parasite's biological cycle, thus preventing human and animal infection. Therefore, in Brasil the main control measure has been the carcass inspection during the slaughter, which is also the most common diagnostic practice. Insufficient T. saginata molecular information makes difficult consistent advances to the improvement of diagnostic tests, vaccine development and the identification of new drugs for treatment. In order to gain insights about the parasite's metacestode developmental stage, RNAseq technology was used to assemble the whole transcriptome of a T. saginata metacestode. These data will also be useful for the next generation screening studies of diagnostic and immunoprophylatic markers for bovine cysticercosis